Axillary Brachial Plexus Block With Patient Controlled Analgesia for Complex Regional Pain Syndrome Type I: A Case Report. Issue 1 (1st January 2001) - Wang, Li-Kai; Chen, Han-Ping; Chang, Pei-Jung; Kang, Fu-Chi; Tsai, Yu-Chuan
Abstract : Background and Objectives: Brachial plexus block (BPB) has been cited as a treatment modality for complex regional pain syndrome type I (CRPS I) of the upper limb. However, there are no reports using axillary BPB with patient controlled analgesia (PCA) for the treatment of CRPS I. This report is based on the retrospective observations of the outcome and effects of axillary BPB with PCA in a patient with CRPS I. Case Report: A 32-year-old man suffered from CRPS I of the right upper limb after surgical release of carpal tunnel syndrome of the right hand. Symptoms and signs over the right hand were alleviated under rehabilitation and conventional pharmacological management, but severe painful swelling of the right wrist persisted. Axillary BPB with PCA was performed on the 32nd postoperative day, which soon resulted in significant reduction of pain with gradual improvement of function of the right wrist. Conclusions: Axillary BPB with PCA may provide patients with CRPS I of the upper limb a feasible and effective treatment. Reg Anesth Pain Med 2001;26:68-71.